2017
DOI: 10.1002/ijc.30529
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐protease inhibitors for the treatment of cancer: Repositioning HIV protease inhibitors while developing more potent NO‐hybridized derivatives?

Abstract: The possible use of HIV protease inhibitors (HIV-PI) as new therapeutic option for the treatment of cancer primarily originated from their success in treating HIV-related Kaposi's sarcoma (KS). While these findings were initially attributed to immune reconstitution and better control of oncogenic viral infections, the number of reports on solid tumors, KS, lymphoma, fibrosarcoma, multiple myeloma and prostate cancer suggest other mechanisms for the anti-neoplastic activity of PIs. However, a major drawback for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 104 publications
3
55
0
Order By: Relevance
“…PIs induce cell growth arrest, endoplasmic reticulum stress, caspase‐dependent apoptosis, autophagy (for review see). Moreover, PIs are known for their antiangiogenic and radiosensitizing effects . PIs action is associated with inhibition of phosphatidylinositol 3‐kinase (PI3K)/Akt pathway; one of the possible mechanisms is binding to Hsp90 and inhibiting its chaperone function followed by decreased PI3K/Akt signaling .…”
Section: Preclinical Antineoplastic Activity Of Haart Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…PIs induce cell growth arrest, endoplasmic reticulum stress, caspase‐dependent apoptosis, autophagy (for review see). Moreover, PIs are known for their antiangiogenic and radiosensitizing effects . PIs action is associated with inhibition of phosphatidylinositol 3‐kinase (PI3K)/Akt pathway; one of the possible mechanisms is binding to Hsp90 and inhibiting its chaperone function followed by decreased PI3K/Akt signaling .…”
Section: Preclinical Antineoplastic Activity Of Haart Drugsmentioning
confidence: 99%
“…Detailed docking analysis has shown that PIs can be potent Hsp90 inhibitors; their binding capacity to Hsp90 decreases in the following order: Nelfinavir, Indinavir, Saquinavir, Ritonavir, Lopinavir, Tipranavir, Darunavir and Amprenavir§ . Indeed, among all PIs, nelfinavir seems to have the highest anticancer activity . It is noteworthy that a longitudinal study of antitumor effects of PIs and especially, nelfinavir, is nuanced by the fact that in 2007 Roche's Viracept (nelfinavir mesylate) was discovered to be contaminated by a mutagenic compound .…”
Section: Preclinical Antineoplastic Activity Of Haart Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a phase I a clinical trial of NFV against various adult solid tumors also showed partial responses in up to 3 of 11 of evaluable patients with drug safety and tolerability 15. Additionally, there is some preclinical work on PI-derivatives showing promising results, including in leukemia 1922…”
Section: Introductionmentioning
confidence: 99%